Fluoroquinolone resistance mechanisms in an Escherichia coli isolate, HUE1, without quinolone resistance-determining region mutations - Sato, Toyotaka; Yokota, Shin-ichi; Uchida, Ikuo; Okubo, Torahiko; Usui, Masaru; Kusumoto, Masahiro; Akiba, Masato; Fujii, Nobuhiro; Tamura, Yutaka (Frontiers in Microbiology, 2013)
Fluoroquinolone resistance can cause major clinical problems. Here, we investigated fluoroquinolone resistance mechanisms in a clinical Escherichia coli isolate, HUE1, which had no mutations quinolone resistance-determining regions (QRDRs) of DNA gyrase and topoisomerase IV. HUE1 demonstrated MICs that exceeded the breakpoints for ciprofloxacin, levofloxacin, and norfloxacin. HUE1 harbored oqxAB and qnrS1 on distinct plasmids. In addition, it exhibited lower intracellular ciprofloxacin concentrations and higher mRNA expression levels of efflux pumps and their global activators than did reference strains. The genes encoding AcrR (local AcrAB repressor) and MarR (MarA repressor) were disrupted by insertion of the transposon IS3-IS629 and a frameshift mutation, respectively. A series of mutants derived from HUE1 were obtained by plasmid curing and gene knockout using homologous recombination. Compared to the MICs of the parent strain HUE1, the fluoroquinolone MICs of these mutants indicated that qnrS1, oqxAB, acrAB, acrF, acrD, mdtK, mdfA, and tolC contributed to the reduced susceptibility to fluoroquinolone in HUE1. Therefore, fluoroquinolone resistance in HUE1 is caused by concomitant acquisition of QnrS1 and OqxAB and overexpression of AcrAB−TolC and other chromosome-encoded efflux pumps. Thus, we have demonstrated that QRDR mutations are not absolutely necessary for acquiring fluoroquinolone resistance in E. coli.